O recurso extraordinário e a emenda constitucional nº 45/2004: uma abordagem teleológica da nova configuração constitucional e processual civil - Costa, Hélio Rubens Batista Ribeiro (2008)
Throuhgout this dissertation, we will study the proper paper of the Supreme Federal Court, as agency of cupola of the Judiciary Brazilian and its vocation - modern - of acting as a Constitutional Court. To reach the intended desideratum, a depp study regarding the Supreme Federal Court will be developed based on historical and, as forecast of the Constitution of the Federative Republic of Brazil, the ability, the organization, the structure and the composition of the court. These subjects have, even though some indirectly, a link with the appeals process of the Brazilian Supreme Court. As the general lines regarding the Supreme Federal Court are traced, the dissertaion will explore the appeals process of the Brazilian Supreme Court considering the historical origins of the institute - flowing also under the support of the foreign law - and its main aspects and points of doctrinal interest, scuh as the processing, the prequestioning, the communication of "supersedeas", the execution that if processes while hanging its judgment and the rescission of the sentence in pronounced it. Along this paper, we will explore the control of constitutionality of the laws and the nornativs acts of the Public Power in one side and the question of the "binding abridgement"in another side. Finally, we will focus on the new roupagem of the appeals process of the Brazilian Supreme Court - if they detach the justinian codes of the prequestioning, of the general repercussion, as well as its concept, law nature, hypotheses of cabiment and the right to sumular referring it. This dissertation will make a detailed study of the legilative evolution concernents of the object of the work and, of sufficiently intense form. It will also examine the evolution of the jurisprudence of the Supreme Federal Court. Sentences pronounced by the Supreme one since times (sufficiently) past until the present will be analyzed, looking for to demonstrate the jurisprudencial evolution, the positioning of the Court, the respects of the main points of the work, as they are - in special - the "binding abridgement", the general repercussion and the modulation of the effect in the judgments of the court. During the chapter exploring the "binding abridgement" not only will be analyzed the general theory of the institute and the law of regency but also the principals will be coment verbets of the compendium of the Supreme Federal Court; its "usual" abridgement ( without the binding effect), that they say respect to the interposition, processing and judgment of the appeal to the Brazilian Supreme Court. The three initials will also be commented verbets of just implemented abridgement with binding effectiveness of the court. The general repercussion of turned constitutional question in the appeal to the Brazilian Supreme Court will be analyzed of one retrospect inside historical, when - exactly that without bigger intentions - to compare itself with the institute of the petition for certionari of past systems constitutional. It will also be analyzed in function of the foreign law, with small study (to the times comparative) with the North American right and institute of certorari. All the legislative set where inserted the general repercussion will be analyzed, of Constitutional Emendation Regimental n. 45/2004 to the Emendation Regimental-STF n. 21, that it disciplines it in the scope of the court. The initial decisions will be analyzed still that are, nowadays, concepts and forming them pillars of the institute, in the vision of the Supreme Federal Court. As everything how much it rees-echo, it reverberates positive negative or, the work will develop an item of that it has not cogitated the doctrine: the "" negative "" positive "general repercussion" as or as - and will explore, in this direction, the viability of such nomenclatures and until its effect. The modulation of the effect, wants if it integrates in the context of the intent control of unconstitutionality, wants it belongs to the diffuse control, minudentement will be analyzed. In this part, the work will analyze the jurisprudencial evolution of the institute in the Supreme Federal Court, making sweepings of the main decisions that have applied it or referenciad. Of form to not only demonstrate the jurisprudence of the court, but and mainly the evolution of the institute of the modulation of the effect to the long one of the times until the present. With the advent of art. 27 of Law 9,868/99 (that explicitament it foresees and it allows the posssibilite of the modulation of the effect in the judgments of direct actions of unconstitutionality), the institute took great breath in the supreme instance. It will be perceived that in some cases - and they they will be commented - of fact the Supreme Federal Court more of the one than necessary, must, to launch hand of possibilite in it checked so that its judgment is to one alone certain time, legal, just, efficient, productive - and accepted for the society. The modulation of the effect seems to be primordial item in the agenda of the Supreme Federal Court, also inside of the perspective of a constitutional jurisdiction. Subjects as the partisan allegiance cannot be analyzed under the influx of the modulation. As well as subjects in the Supreme Federal Court, many of them of bias tributary, as we will be able to observe in the course of the work, also are to demand a differentiated behavior of judgment. By the way, the work will not be stolen to examine an adjacent point in the context of the modulation of the effect: the possibility of the institute to be applied in the judgments of the Superior Courts. So controversial how much the question of the modulation of the effect in the constitutionality judgments will have of being our proposal of professional qualification for the practice of law in Superior Courts. One and another one - however - will be developed with the maximum intellectual honesty and in accordance with logical and coherent premises, exactly that - of remaining portion and in more - some can not agree to specific conclusions on these two particular - and controversial - of the work. We will present data of interest on the brazilian Judiciary Power - and, more necessarily, of proper the Supreme Federal Court and the appeal to the Brazilian Supreme Court, one of the vehicles that in it park. The study he will develop, still, some suggestions of uniformization of application of the common concepts to the processing of the kind of appeal Brazilian Supreme Court, therefore in many times the Supreme Federal Court and the Superior Court of Justice have different positionings regarding one same subject as, for example, the concept of prequestioning, its division in implicit and explicit and the regimen of the action for a provisional remedy ones for the loan of "supersedeas" to the appeals to the Brazilian Supreme Court and special, respectively. Finally, and always that opportune, the work will present suggestions of lege ferenda